Macrozoobenthos in the Adriatic Sea ports: Soft-bottom communities with an overview of non-indigenous species. (October 2019) - Travizi, A.; Balković, I.; Bacci, T.; Bertasi, F.; Cuicchi, C.; Flander-Putrle, V.; Grati, F.; Grossi, L.; Jaklin, A.; Lipej, L.; Mavrič, B.; Mikac, B.; et al.
Abstract: The present paper is a contribution to the first initiative of the Port Baseline Survey (PBS) for Non-indigenous species (NIS) in the Mediterranean Sea. It presents a report on the soft-bottom macrobenthos from the five Adriatic ports: Bari, Ancona (Italy), Koper (Slovenia), Pula, Rijeka (Croatia), with a focus on the presence and contribution of NIS to native assemblages. Out of 451 species identified, only four were common to all ports. A total of eight NIS were recorded, five in surveyed ports and three in the lagoon connected to the Port of Koper. The highest number of NIS was recorded in Bari, and the highest abundance in Ancona and Bari. Generally, the number, abundance and contribution of NIS seems too low to cause a substantial impact on native communities in surveyed ports. The suitability of methods adopted for PBS for soft-bottom NIS was discussed and suggestion for methodological improvement is provided. Highlights: Soft-bottom macrobenthos were investigated from five Adriatic ports. Contribution of Non-indigenous species (NIS) to native assemblages was discussed. Contribution of NIS seems too low to cause a substantial impact on native communities. The suitability of methods adopted for Port Baseline Survey for soft-bottom NIS was discussed. Suggestions for methodological improvement are provided.